Effectiveness of computer-assisted cognitive training on cognitive function and activities of daily living in patients with post-stroke cognitive impairment - Feng, Xiaoyang; Sun, Xiaolin; Liu, Jia; Li, Yan; Yao, Yunhai; Fu, Jianming; Gu, Xudong (Frontiers in aging neuroscience, 2025)
ObjectiveThis study aimed to investigate the effects of computer-assisted cognitive training (CACT) on cognitive function and activities of daily living in patients with post-stroke cognitive impairment. Additionally, it aimed to explore the changes in specific cognitive domains before and after treatment.DesignThe study was a double-blind, randomized, controlled trial.SettingIt took place in rehabilitation wards or outpatient clinics.ParticipantsSixty patients with post-stroke cognitive impairment took part in the study.InterventionsParticipants were randomly assigned to either the control (n = 30) or the intervention group (n = 30). Both groups received conventional rehabilitation and cognitive training, and the intervention group additionally received CACT.Main outcome measuresThe primary outcome measures included the Mini-Mental State Examination (MMSE) and event-related potential (ERP) P300 for cognitive function, as well as the modified Barthel Index (MBI) for activities of daily living. Secondary outcomes were the Trail Making Test (TMT), the Symbol-Digit Modalities Test (SDMT), the Auditory Verb Learning Test-Huashan version (AVLT-H), the Boston Naming Test (BNT), and the Clock Drawing Test (CDT), which assessed cognitive function across specific domains.ResultsBoth groups showed significant improvements in MMSE, MBI, amplitude of P300, and latency of P300, with the intervention group demonstrating more pronounced improvements compared to the control group. In terms of specific cognitive domains, the intervention group exhibited greater improvements than the control group in TMT-A, TMT-B, and AVLT-H. Both groups showed improvements in SDMT and BNT, but the differences between the groups were not statistically significant. Additionally, there was no significant improvement in the CDT for either group before and after treatment.ConclusionCACT was found to improve patients’ cognitive function, especially in areas of attention, executive function, and memory. It also effectively improved activities of daily living.